Prospective directions for the development of means and methods for detection and fixation of handprints - V. V. Korniienko (Law and Safety)
Identification by fingerprints remains one of the most common ways of proving the involvement of persons in the commission of a criminal offense in law enforcement practice around the world. Over the past hundred years, the methodology of detecting and collecting fingerprints at the scene has evolved from the first attempts to use carbon black and metal powders (at the end of the 19th century) to the use of modern fluorescent powders and molecularly selective chemical compounds.